Features of the Foreign Policy of Hungary and the Visegrad Countries - Nyilas, Laura (Medzinárodné vzťahy, 2024)
The study aims to explore the changing perception of the Visegrad countries' external relations in the current security environment, with a special focus on Hungary. The study aims to challenge perceptions of the group's divergence by shedding light on the presence of shared partners in their external contacts, notwithstanding recent accusations that show frictions in the Visegrad Group's collaboration and even call into question the group's very existence. By identifying the common and significant partners in external relations, both collectively and separately, the study seeks to illustrate the cooperation and the orientation of each country towards the East or the West, with a particular focus on Hungary's position in this regard. The study also aims to support the hypothesis that these common strategic partners can provide valuable insights into the future direction of Visegrad Cooperation. Through the analysis, the study provides a comprehensive picture of the Visegrad countries' external relations and their impact on regional cooperation and security, illustrating the cooperation and highlighting Hungary's position in the international world order.